Menelusuri Faktor-Faktor Penentu Keputusan Pembelian: Studi Kasus Konsumen GrabFood di Samarinda - Kusrihandayani, Dyah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Abstract This study aims to examine the influence of price, promotion, ease of use, and brand image on consumer purchasing decisions for the GrabFood delivery service in Samarinda. The research sample consists of 100 respondents who are active GrabFood users in Samarinda, selected using a purposive sampling method. The results of multiple regression analysis indicate that all independent variables—price, promotion, ease of use, and brand image—have a significant effect on purchasing decisions. These findings underscore the importance of implementing targeted promotional strategies to enhance purchase intention, particularly among users of the GrabFood delivery service. Therefore, the results of this study can serve as a reference for e-commerce players in formulating more effective marketing strategies to influence consumer purchasing behavior. Keywords: Price, Promotion, Ease of Use, Brand Image, Purchase Decision